تحسين أنظمة التعرف على الكلام عن طريق جمع خوارزميتين لاستخلاص السمات - جعفر الخير (Tishreen University, 2018)
تعد تقنيات التعرف على الكلام من أهم التقنيات الحديثة التي دخلت بقوة في مجالات الحياة المختلفة سواء الطبية أو الأمنية أو الصناعية. وبناءً عليه تم تطوير العديد من الأنظمة المعتمدة على طرق مختلفة في استخلاص السمات و التصنيف. في هذا البحث تم إنشاء ثلاثة أنظمة للتعرف على الكلام، تختلف عن بعضها البعض بالطرق المستخدمة في مرحلة استخلاص السمات،حيث استخدم النظام الأول خوارزمية MFCCبينما استخدم النظام الثاني خوارزمية LPCCأما النظام الثالث فاستخدم خوارزمية PLP.تشترك هذه الأنظمة بطريقة التصنيف حيث استخدمت خوارزمية الـHMM كمصنف. في البداية تم دراسة وتقييم أداء عملية التعرف على الكلام للأنظمة الثلاثة السابقة المقترحة منفردةً. بعد ذلك تم تطبيق خوارزمية الجمع على كل زوج من الأنظمة المدروسة وذلك لدراسة أثر خوارزمية الجمع في تحسين التعرف على الكلام. تم اعتماد نوعين من الأخطاء، الأخطاء التزامنية (simultaneous errors) والأخطاء الاعتمادية ((dependent errors، كوحدة مقارنة لدراسة فعالية خوارزمية الجمع في تحسين أداء عملية التعرف على الكلام. يتبين من نتائج المقارنة أن أفضل نسبة تعرف على الكلام تم الحصول عليها في حالة جمع الخوارزميتان MFCC وPLPحيث تم الحصول على معدل تعرف 93.4%. The speech recognition is one of the most modern technologies, which entered force in various fields of life, whether medical or security or industrial techniques. Accordingly, many related systems were developed, which differ from each otherin feature extraction methods and classification methods. In this research,three systems have been created for speech recognition.They differ from each other in the used methods during the stage of features extraction.While the first system used MFCC algorithm, the second system used LPCC algorithm, and the third system used PLP algorithm.All these three systems used HMM as classifier. At the first, the performance of the speechrecognitionprocesswas studied and evaluatedfor all the proposedsystems separately. After that, the combination algorithm was applied separately on eachpair of the studied system algorithmsin order to study the effect of using the combination algorithm onthe improvement of the speech recognition process. Twokinds of errors(simultaneous errors and dependent errors) were usedto evaluate the complementaryof each pair of the studied systems, and to study the effectiveness of the combination on improving the performance of speech recognition process. It can be seen from the results of the comparison that the best improvement ratio of speech recognition has been obtained in the case of collection MFCC and PLP algorithms with recognition ratio of 93.4%.